Pengaruh Tingkat Kepuasan Petani Mangga Podang Terhadap Kinerja Penyuluh Pertanian Lapang Di Kecamatan Banyakan Kabupaten Kediri - Atmiko, Diyat; Tiyas, Ratna Dewi Mulyaning; Laksono, Sonny Subroto Maheri (Universitas Islam Kadiri, 2024)
The agricultural sector is one of the dominant sectors that affects the income of the Indonesian people. One of Indonesia's agricultural commodities is mango. Dinas Pertanian dan Perkebunan Kabupaten Kediri trying to increase yields and quality of agricultural, one of them is mango podang are agricultural products can be unseeded in Kecamatan Banyakan Kabupaten Kediri. The performance of agricultural extension can be measured by the level of satisfaction farmers to obtain information from agricultural extension. In general there is information that the agricultural extension could not give information optimally for farmers and the farmers. so it is necessary to conduct research on: The Effect of Level Of Satisfaction Farmers Mango Podang on Agricultural Extension Performance Kecamatan Banyakan Kabupaten Kediri. This research was a quantitative research the data collection methods used were questionnaire, literature, observation, interview, and documentation. The data analysis used was descriptive analysis and simple linier regression with variable Level Of Satisfaction Farmers and Agricultural Extension Performance. The result of the analysis using IBM SPSS Statistic 25 showed the linier regression analysis result of Y = 5.377 + 1.253X and t-value (10,957) > t-table (2,010) with the coefficient of determination of 0.714. This indicated that the 71,4% of Agricultural Extension Performance was affected by Level Of Satisfaction Farmers Mango Podang and the remaining 28,6% was affected by other factors not explained in this research.